Социальная структура и личность в процессе радикальных изменений: анализ Украины в период трансформаций - Кон, М.; Хмелько, В.; Паниотто, В.; Хунг Хо-Фунг (Социология: теория, методы, маркетинг, 2005)
This paper investigates the relationships of social structure and personality during a
period of radical social change attendant on the early stages of the transformation of
Ukraine from socialism to nascent capitalism. It does so by analyzing data secured
from face to face interviews with a representative sample of urban Ukrainian men
and women in 1992 93, together with a follow up survey three to three and a half
years later of all those respondents who at the time of the initial survey either were
employed or were seeking paid employment. We found that the over time correlations
— the stabilities — of two underlying dimensions of personality — self -directedness of
orientation and a sense of well being or distress — were startlingly low, by comparison
not only to the United States at a time of much greater social stability, but also to
Poland at the same time as the Ukrainian study, albeit at a later stage of transition. The
stability of a third fundamental dimension of personality — intellectual flexibility —
was higher than those of self directedness of orientation and distress, but considerably
lower than past research had led us to expect. Still, despite massive changes in social
and economic conditions and great instability of personality, the relationships of
social structure with personality were remarkably consistent over time and, with the
partial exception of those with the sense of wellbeing or distress, were quite similar to
those of both socialist and advanced capitalist societies during times of apparent
social stability. Our analyses suggest that consistency in the relationships between
social structure and personality despite great change both in social structure and in
personality results from the continued stability of proximate conditions of life that link
position in the larger social structure to individual personality, and the continued
strength of those linkages. Notable among these proximate conditions, for those people
who were employed at the times of both the baseline and follow up surveys, is the
substantive complexity of their work.